Parameter determination for efficient vowel mapping of English loan words to the Filipino language - Cristobal, Elaine Rose N.
The Filipino language borrows words from other languages such as English. These words are called loan words and they are borrowed with little or no change to the spelling and pronunciation. In determining the spelling of the load words, it is necessary to have a standard. Spelling standards associated with the consonants of the Filipino language have already been established. However, no such standard exists for the vowels. The objective of this project is to be able to provide scientific aid in creating the spelling standard for loan word vowels. Particularly, we aim to determine the parameters or features that will be used to create a mapping between the 20 English vowels found in the TIMIT Speech Corpus and the 5 Filipino vowels found in the Filipino Speech Corpus (FSC). Preliminary analysis was done on the English vowels found in the TIMIT database as well as on the Filipino vowels of the FSC. This allowed an initial inspection on the similarities of the vowels. Then, two sets recordings of the loan words were done. Energy-based vowel detection allowed automated delineation of the vowels. Feature extraction was done on the vowels of the load words. Statistical methods were then used on the features to create a vowel mapping between the loan words vowels and the Filipino vowels. Two features of speech were found to be viable in creating the vowel mapping. One is the formants which are the resonating frequencies of the human vocal tract. The first two formants F1 and F2 were used. Another feature is the Mel frequency cepstral coefficients (MFCC) which takes into consideration the processes of human hearing. A vowel mapping was created using the two features F1-F2 and MFCC. This mapping will be used by the Sentro ng Wikang Filipino to aid them in formulating the spelling standard for English loan words.